2019
DOI: 10.1515/ans-2019-2069
|View full text |Cite
|
Sign up to set email alerts
|

Regularity Properties for a Class of Non-uniformly Elliptic Isaacs Operators

Abstract: Here we consider the elliptic differential operator defined as the sum of the minimum and the maximum eigenvalue of the Hessian matrix, which can be viewed as a degenerate elliptic Isaacs operator in dimension larger than two. Despite of nonlinearity, degeneracy, non-concavity and non-convexity, such operator generally enjoys the qualitative properties of the Laplace operator, as for instance maximum and comparison principle, Liouville theorem for subsolutions or supersolutions, ABP and Harnack inequalities. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
(80 reference statements)
1
9
0
Order By: Relevance
“…We end this note by pointing out that the regularity issue for solutions of (1.1) in the case a 1 = 0 and a N > 0 (or a 1 > 0 and a N = 0) is an open problem and only partial results are known: Lipschitz regularity for P ± 1 , see [2], Hölder estimates for M a in the case of asymmetric distributions of weights concentrated on the smallest or on the largest eigenvalue, namely a 1 > a 2 + • • • + a N or a N > a 1 + • • • + a N −1 , see [15] and the references therein.…”
Section: Lack Of Regularitymentioning
confidence: 99%
See 3 more Smart Citations
“…We end this note by pointing out that the regularity issue for solutions of (1.1) in the case a 1 = 0 and a N > 0 (or a 1 > 0 and a N = 0) is an open problem and only partial results are known: Lipschitz regularity for P ± 1 , see [2], Hölder estimates for M a in the case of asymmetric distributions of weights concentrated on the smallest or on the largest eigenvalue, namely a 1 > a 2 + • • • + a N or a N > a 1 + • • • + a N −1 , see [15] and the references therein.…”
Section: Lack Of Regularitymentioning
confidence: 99%
“…Let us point out that our result does not apply to P ± k when k < N since in these cases a 1 or a N are zero. Nevertheless, some regularity results concerning such operators, in particular for k = 1, can be found in [19] and [2, Propositions 3.1-3.2]- [15,Theorem 1.4]. Applying the Ishii-Lions approach to the problem (see [20]), we manage to prove that viscosity solutions of (1.1) are C 0,β loc (Ω), where…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…In general, the PDE (1.2) is fully nonlinear and not uniformly elliptic, and we do not get Hölder regularity directly from the general theory. For this equation with lower order terms, Ferrari and Vitolo [FV20] used methods from the viscosity theory to study ABP, Harnack and Hölder estimates, and later Ferrari and Galise [FG21] showed C 0,δ -regularity for 0…”
mentioning
confidence: 99%